Evaluating “West Kalimantan Culinary Book” as A Supplementary Book for Undergraduate Students - Stella Prancisca; Ana Fergina (STKIP Singkawang, 2020)
The present research believes that teaching materials which promote Indonesian traditional heritages should be available for students both inside and outside the classroom. For this reason, the research aims to preserve the presence of local cultures in the mid of English culture’s popularity by developing a book which contains aformentioned topics. The outcome of this empirical research is a textbook used as media for extensive reading in the student’s pleasure time. Using the ADDIE approach, this research collected data from several undergraduate students currently studying at a state university in Indonesia. The students were requested to read the West Kalimantan Culinary Book and share their ideas on what they have just read. In addition, the book was evaluated by experts from linguistic and cultural fields. The student’s feedbacks were very useful as they would reflect a potential user’s view in the future. Meanwhile, evaluations from experts helped us verify if the book was developed properly. Results indicated that readers responded to this culinary book positively. The book was considered helpful and unique as it was written in the English language. Since the book was aimed for extensive reading materials, we also checked and confirmed that this book followed the principles of extensive reading expressed by Day and Bamford (2002). To conclude, the research indicates its limitation particularly in terms of generalisability and provides suggestions for further research in order to improve the instruments of the data collection.